2017
DOI: 10.1007/s41233-017-0007-4
|View full text |Cite
|
Sign up to set email alerts
|

An extensive performance evaluation of full-reference HDR image quality metrics

Abstract: High dynamic range (HDR) image and video technology has recently attracted a great deal of attention in the multimedia community, as a mean to produce truly realistic video and further improve the quality of experience (QoE) of emerging multimedia services. In this context, measuring the quality of compressed HDR content plays a fundamental role. However, full-reference (FR) HDR visual quality assessment poses new challenges with respect to the conventional low dynamic range case. Quality metrics have to be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 49 publications
1
59
1
Order By: Relevance
“…While this aggregation of subjective quality scores is usually done for rating (i.e. mean opinion scores) [1], [2], [19] or pairwise comparisons [20], [21] individually, little has been done to study the fusion of scores obtained by both these two methodologies. In this regard, Ye and Doermann [17] proposed a unified probabilistic model, aggregating rating and pairwise comparisons together.…”
Section: B Fusing Rating and Pairwise Comparisons Datamentioning
confidence: 99%
See 1 more Smart Citation
“…While this aggregation of subjective quality scores is usually done for rating (i.e. mean opinion scores) [1], [2], [19] or pairwise comparisons [20], [21] individually, little has been done to study the fusion of scores obtained by both these two methodologies. In this regard, Ye and Doermann [17] proposed a unified probabilistic model, aggregating rating and pairwise comparisons together.…”
Section: B Fusing Rating and Pairwise Comparisons Datamentioning
confidence: 99%
“…For example, an image rated 4 on a 5-point scale in one experiment could be rated 2 in another experiment because of differences in the training, range and type of considered distortions. Dealing with widely different scales when training quality metrics is problematic, often requires using rank-order correlation as a measure of prediction accuracy, and makes difficult the use of multiple datasets for training [1], [2]. M. Pérez-Ortiz and A.…”
Section: Introductionmentioning
confidence: 99%
“…In addition those databases are composed of a rather small amount of images. To obtain a suitable database for our experiment, we considered the five databases presented in Table 1: Narwaria et al [21], Korshunov et al [22], Zerman et al [23], 4Kdtb [11] and HDdtb [18]. The first four databases were used for the training phase and HDdtb was considered as an independent test database used to validate our proposed metric.…”
Section: Image Quality Databasesmentioning
confidence: 99%
“…1) Content creation: Eight images were selected from 3 collections: two are from the MPEG HDR sequences (FireEater and Market) [14], one is from the Stuttgart HDR Video Database [3] and the remaining five images comes from HDR photographic survey [2]. Note that these images also belong to Zerman et al's database [24]. All these images have been encapsulated in the WCG gamut BT.2020 [9] instead of the standard gamut BT.709 [8].…”
Section: B a New Databasementioning
confidence: 99%
“…In [6], authors came to the conclusion that HDR-VDP2 (but in an earlier version 2.1.1) can be successfully used for predicting the quality of video pair comparison contrary to HDR-VQM. More recently, Zerman et al [24], first, combined several existing image databases and, second, they found out that HDR-VQM is the best full-reference HDR quality metric, closely followed by the HDR-VDP2.2.1 metric which gives similar results when one particular database is discarded.…”
Section: Introductionmentioning
confidence: 99%